Innovative guidelines and tools for vulnerable road users safety in India and Brazil [SaferBraIn]: D3.4 Decision Supporting System - Antonino Tripodi; Claire Quigley; Ruth Sims; Martijn van de Leur; Angela van der Kloof; Alessandro Fornasiero; Roberto Carroccia (2011)
The document provides an overview of objectives, characteristics, functions of the DSS, as well as a guide for its use.